The effects of game-based virtual reality application on labor pain and childbirth satisfaction in primiparous pregnant women: A randomized controlled study - Sunay, Zeliha; Ucar, Tuba (Taylor & Francis Inc, 2025)
We conducted this randomized controlled experimental study to determine the effects of game-based virtual reality (VR) applications on labor pain and childbirth satisfaction in 120 primiparous pregnant women. The intervention group received game-based VR intervention combined with non-pharmacological methods for managing labor pain, while the control group received routine care. In comparison to the control group, the intervention group had significantly lower pain levels (p < 0.001) and significantly higher childbirth satisfaction levels (p < 0.001). According to our findings, the use of game-based VR was associated with reduced labor pain and increased childbirth satisfaction, suggesting its potential as an innovative approach to improving maternal health outcomes globally.
Keywords: Anxiety; Music; Management; Birth